Truth-telling with a smartphone: The effect of communication media in strategic interactions - Cartwright, Edward; Xue, Lian (Frontiers in Behavioral Economics, 2023)
Technological advancements have transferred our business as well as social interactions. A recent trend is the increasing use of smartphones for work and customer engagement. Given that smartphones have been associated with a heightened sense of personal ownership and moral disengagement we argue that this may have negative implications for ethical behavior. To evaluate this conjecture we ran an experiment comparing dishonesty when using pen and paper, a desktop computer, or a smartphone. We make this comparison in both a setting where dishonesty bene ts another (mutual-gain) and one where it harms another (constant-sum). We nd higher levels of dishonesty when using a smartphone than pen and paper. We nd relatively high levels of dishonesty when using a desktop computer in the mutual-gain setting but low levels in the constant-sum setting. Our results are consistent with the conjecture that smartphone use can lead to less ethical behavior.